Outcomes of Treatment for Melanoma Brain Metastases - Mantas Janavicius; Nadezda Lachej; Giedre Anglickiene; Ieva Vincerzevskiene; Birute Brasiuniene (Journal of Skin Cancer)
Background. Historically, melanoma with brain metastases has a poor prognosis. In this retrospective medical record review, we report basic clinicopathological parameters and the outcomes of patients with melanoma and brain metastases treated with different treatment modalities before the era of immunotherapy and modern radiotherapy technique. Methods. Patients with metastatic melanoma were treated with surgery, radiotherapy, and/or systemic therapy from 1998 to 2017. In our study, they were identified and stratified depending on treatment methods. Overall survival was defined as the time from the date of brain metastases to the death or last follow-up (2019 June 1st). Survival curves were estimated using the Kaplan–Meier method that was employed to calculate the hazard ratio. Results. Six (12%) of 50 patients are still alive as of the last follow-up. The median overall survival from the onset of brain metastases was 11 months. The longest survival time was observed in patients treated by surgery followed by radiotherapy, surgery followed by radiotherapy and systemic therapy, and also radiotherapy followed by systemic therapy. The shortest survival was observed in the best supportive care group and patients treated by systemic therapy only. Conclusions. Patients with brain metastases achieved better overall survival when treated by combined treatment modalities: surgery followed by radiotherapy (26.6 months overall survival), combining surgery, radiotherapy, and systemic therapy (18.7 months overall survival), and also radiotherapy followed by systemic therapy (13.8 months overall survival).